HUBUNGAN ANTARA KANDUNGAN LIGNIN KULIT BENIH DENGAN SIFAT-SIFAT KHUSUS KULIT BENIH KACANG HIJAU - Marwanto Marwanto (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2007)
Lignin content in seed coat may have a direct effect on seed coat characteristics of mung bean genotypes (Vigna radiata). This research was designed to study the variation of seed coat lignin content among mung bean genotypes and its relationship to permeability, seed electrolyte conductivity and hard seed. Seeds of eleven mung bean genotypes were grown in research plots at Agriculture Faculty, Bengkulu University on February 2002 and hand harvested at R8 maturation stage. The plots were arranged in a randomized complete block design having three replications. Genotypic differences were evident for seed coat lignin content, seed coat permeability, seed electrolyte conductivity and hard seed. The seed coat lignin content contributed to variability in permeability, seed electrolyte conductivity and hard seed and closely related with permeability (r =0.75*), with seed electrolyte conductivity (r = - 0.93**) and with hard seed (r = - 0.71*). Overall, seed coat lignin content appears to have determining effects on seed coat characteristics.